Effects of Green Light Supplementation with Red and Blue Combinations of LED Light Spectrums On The Growth of Chlamydomonas Reinhardtii (Chlorophyta) - Dina Nabil Mohammed Aljamili; Murat Telli (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Light management strategy regarding optimum spectral composition is a critical factor in microalgae cultivation to improve biomass and biosynthesis of valuable bioactive compounds. Recent advance in LED light technology provides unparallel opportunity to test effects of specific wavelength on physiological response of algae. In this study, we investigated effects of white, monochromatic and combination of red (628 nm) and blue (462 nm) light in the ratio of 1: 1; 2: 1 and 1: 2 at the total light intensity of 40 μmol photons m-2 s-1 on the growth of Chlamydomonas reinhardtii. Moreover, effects of green light (518 nm) supplementation on growth of algae, green light (518 nm) was added gradually into the combination of red:blue (1:2) at the light intensity of 3, 6, 9, 12 and 15 μmol photons m-2 s-1 as an expense of red and blue light intensity at the ratio of 1:2. Results reveal that growth rate of C. reinhadhtii was found in the order of red:blue (1: 2) gt; red:blue (2: 1) gt; red:blue (1: 1) gt; red gt; white gt; blue. Green light supplementation applied as 3 μmol photons m-2 s-1 resulted in statistically significant higher optical density and dry weight than R:B (1: 2) used as control group in the experiment. Chlorophyll-a concentrations were found significantly higher in all green light supplementation than control group. Seems that 3 μmol photons m-2 s-1 supplementation of green light together with red:blue combination results in a significant promotion on growth rate, chlorophyll-a and dry weight of C. reinhardtii.